Combining neurofeedback training and dhikr as adjuvant therapy for treating adolescent depression: a case report - Nugroho, I. Gusti Bagus Indro; Suwito, Djoko; Oktaviyantini, Tri (International Journal of Research in Medical Sciences, 2024)
Depression in adolescents is a significant mental health issue requiring effective therapeutic approaches. This case report evaluates the effectiveness of neurofeedback training and dhikr as adjuvant therapies for a 17-year-old female adolescent diagnosed with bipolar affective disorder, current episode severe depression with psychotic features. The subject underwent eight sessions of combined neurofeedback and dhikr therapy, which showed positive results. Initially, the subject experienced severe sadness, guilt, suicidal ideation, and auditory hallucinations. After the therapy, there was a significant reduction in depressive symptoms and an improvement in mental well-being. Evaluations using quantitative electroencephalography (QEEG) and PHQ-A assessments showed improvements in brain wave activity and a reduction in depression scores from 16 (moderate to severe depression) to 8 (mild to moderate depression). The subject reported feeling calmer, less sad, and showed increased academic and social motivation. These results indicate that the combination of neurofeedback and dhikr can be an effective approach in managing adolescent depression by addressing both psychological and spiritual aspects. Further studies are needed to confirm these findings and explore the underlying mechanisms of this therapy's effectiveness.